Effects of Recombinant Human Tumor Necrosis Factor-α and Its Combination with Native Human Leukocyte Interferon-α on P3-X63- Ag8.653 Mouse Myeloma Cell Growth - Plesničar, Andrej; Vidmar, Gaj; Štabuc, Borut; Plesničar, Blanka Kores (IntechOpen, 2012)
None